THE BAN ON FOREIGNERS ACQUIRING PROPERTY RIGHTS ON AGRICULTURAL АND FOREST LAND IN SERBIA AND OTHER REGION COUNTRIES - Baturan, Luka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In Serbia it is prescribed that foreign legal or natural persons could not become owners of agricultural land, while in Montenegro, Croatia and The Federation of Bosnia and Hercegovina there is the ban for both agricultural and forest land. The aim of this paper is to show that such a ban creates an economic environment where an optimal allocation of agricultural and forest land as a production factor could not be achieved. The cost - benefit analysis shows that main gainers are domestic producers and buyers of land who are able to realize a monopoly profit, whereas sellers of land are at loss, getting a lower economic rent, as well as foreign buyers. A total loss of domestic sellers only is bigger than a total profit of buyers. In the end, it is being pointed to a relativity of the ban, in the sense of a possibility to easily get past the ban through provisions of the other norms. The conclusion points out that an eventual suspension of the ban would stimulate efficiency of domestic economies and an increase in the neto welfare.
Keywords: foreigners; property right; forest land; agricultural land